Disharmony of Zakat Profession Nisab in Regional Zakat Management Organizations: Regulatory Impact Analysis (RIA) Based on the Minister of Religious Affairs Regulation of the Republic of Indonesia Number 31 of 2019 - Budiarto, Muhamad Agung; Rosyadi, Imron (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study examines the inconsistency in the application of zakat profession nisab in regional zakat institutions, particularly those using the silver nisab for zakat obligations, contrasting with the gold nisab in the Minister of Religious Affairs Regulation of the Republic of Indonesia Number 31 of 2019 on Zakat Management. This practice has led to significant differences in administrati ve effectiveness and compliance with Islamic legal principles. The purpose is to analyze the impact of using the silver nisab on legal legitimacy, social justice, and regulatory compliance in zakat institutions. Methodology: This study uses a qualitative descriptive approach through in-depth interviews, institutional policy observation, and regulatory impact analysis (RIA) of PMA No. 31 of 2019. The study analyzes the effects of the silver nisab in zakat instituti ons, focusing on legal and social implications, and how it influences zakat collection and compliance with Islamic law and state regulations. Results: The results indicate that the silver nisab policy expanded the zakat base and increased zakat collection, but reduced compliance with both Islamic law and state regulations. This finding highlights the need for policy adjustments to ensure zakat institutions remain compliant with both sharia and national legal frameworks. Applications/Originality/Value: The study provides valuable insights into the effects of nisabpolicies on zakat collection and compliance. It highlights the need for coordinated policy efforts to balance zakat collection effectiveness with adherence to sharia principles. This research contributes to the understanding of zakat management in Indonesia and offers recommendations for improving zakat compliance.